Improving Physical Fitness Learning Outcomes On Agility Components With Modification Of The Running Squat - Santi, Santi; Indahwati, Nanik; Satria, Sigra Santika (Yayasan Insan Mulia Bima, 2024)
The learning process, which revealed a decline in students' interest in PJOK lectures, served as the impetus for this study. In order to create a very successful learning experience, teachers must be creative. Using a customized version of a simple game is one approach to get around this problem. This study's goal is to ascertain if employing media to alter games for learning can improve learning outcomes and student responses after using modified media for while running games to learn about the game subject. PTK, which is broken down into two cycles with three stages-planning, carrying out, and reflecting-is exemplified by this study. Research subject for Class IX-A SMP Labschool Unesa 3. The completeness of learning outcomes increased, with cycle I being 35.29% with 7 students completing and cycle II amounting to 82.35% with 20 students completing, with an increase percentage of 47.06%. Specificallyan average of 40.3 in the first cycle and 80.0 in the second, with a 39.7 rise. The study's findings demonstrated that pupils' learning outcomes in the squat running game content may be enhanced by using modified squat running games.